(untitled) (UNIZIK Journal of Marketing, 2024)
This paper assessed product segmentation in micro finance banks of Lagos State, Nigeria. To achieve this objective, the study adopted a cross-sectional case method. All the MfBs in Lagos State was considered as the population of the study with six (6) MfBs selected based on their operations, activities and location in senatorial district. Participants in the study were the Managing Directors, Employees, and Customers of the Six MfBs. Convenience sampling technique was adopted. Data gathering was carried out through interview and interview sessions were held at intervals. Results were presented along themes. It was found that there were two (2) core product lines financial products (savings, loan facilities and transfer) and non-financial products (trade, agriculture and assets/housing) in MfBs. It was concluded that MfBs product segmentation has been found to be along two folds namely financial products and non-financial products. However, insignificant numbers of MfBs have explored the non-financial products segmentation as evident in the study. The study recommends that both non-financial and financial products are to be jointly promoted to achieve the essence of MfBs. The study is limited by lack of quantitative data and metrics, and brief customer insights. However, this does not affect the quality of the study as it only gives room for further studies